First Report of a Nematode Pterygodermatites affinis Parasitizing a Stray Cat (Felis catus) from North India - Kumar, Pradeep; Tiwari, Jitendra; Kumar Singh, Alok; Kishor Tiwari, Vinay; Kamal, Tarun (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The genus Pterygodermatites (Order: Spirurida, Family: Rictulariidae) represents a group of spirurid nematodes known for their complex life cycles and wide host range among terrestrial vertebrates. These nematodes are primarily intestinal parasites of small mammals, with the majority of species infecting rodents and insectivores (Anderson et al., 2009). Occasional infestations have also been reported in carnivorous hosts, including wild canids and felids, although such occurrences remain relatively rare. Transmission of Pterygodermatites spp. follows an indirect life cycle involving arthropod intermediate hosts typically cockroaches or beetles which ingest embryonated eggs and in turn are consumed by the definitive mammalian host (Yue et al., 1986; Sundar et al., 2023). While the genus has a cosmopolitan distribution, most documented infections in felids are restricted to regions in Europe and North Africa (Feliu et al., 1997). In felines, infections are often under-diagnosed due to the cryptic nature of parasitism, limited veterinary care for stray animals, and a general lack of targeted parasitological surveillance. Stray cats, in particular, occupy a unique ecological niche. Often unmanaged and lacking routine veterinary attention, they serve as potential reservoirs and transmission agents for a variety of helminth parasites, some of which may pose risks to human and animal health (Alho et al., 2017; Khedri et al., 2024). In India, while several studies have documented the presence of gastrointestinal helminths in stray cats, infections with Pterygodermatites spp. have remained unreported. The absence of previous records may be attributed to limited diagnostic resolution, lack of comprehensive morphological examinations, or true absence of this nematode in local cat populations. The present study fills this gap by documenting, for the first time, the presence of Pterygodermatites affinis in a stray domestic cat (Felis catus) from Mathura, a semi-urban region in northern India characterized by a high density of free-roaming animals and poor waste management. This report contributes new data to the parasitological record, extending both the host range and geographical distribution of P. affinis, and highlights the urgent need for integrated, One Health-based parasitic surveillance in urban and peri urban environments.